Considering Background Condition Effects in Tailoring Tropical Forest Management Systems for Sustainability - Hammond, David S.; Zagt, Roderick J. (Ecology and society, 2006)
Systems devised for managing tropical forests sustainably have yet to prove successful. In many instances, they have fallen short of initial prospects, but the reasons for these shortfalls are often not apparent. Here, we explore factors that can shape the likelihood of success, collectively referred to as background conditions, which are not always adequately considered prior to selecting a suitable management system. We examine the ability of one background condition, geologic terrane, to explain crude spatial variation in a number of trailing indicators of varying forest land use. Forest areas on Precambrian and Phanerozoic terranes show significant differences in production of fossil hydrocarbons, gold, and tropical roundwood, among other indicators, even after considering regional effects. Background conditions are considered to be factors capable of quantifying spatial variation in the likelihood of achieving management success given predefined benchmarks of sustainability. A number of avenues for further exploring and discriminating spatial variation of background conditions are discussed.